Analysis of two phenomenological descriptions of ground-state bands in spherical and closed-shell nuclei - Gorfinkiel, J. L.; Mariscotti, M. J. A.; Pomar, Cayetano (American Physical Society, 1974)
Fil: Gorfinkiel, J. L. Universidad de Buenos Aires; Argentina